PERAN APARAT PENGAWAS INTERN PEMERINTAH (APIP) DALAM PENCEGAHAN PENYALAHGUNAAN PENGELOLAAN KEUANGAN DANA DESA KECAMATAN ATINGGOLA KABUPATEN GORONTALO UTARA - Napu, Suciati; Abdullah, Julie; Saprudin, Saprudin; Masiaga, Novaliastuti (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to examine the role of the Government Internal Supervisory Apparatus (APIP) in preventing the misuse of village fund financial management in Atinggola District. The research employs a descriptive qualitative approach with purposive sampling techniques to obtain in-depth data. The data were analyzed using the interactive model of Miles and Huberman, which includes data collection, data reduction, data display, and conclusion drawing. The findings reveal that APIP's role in routine supervision, counseling and guidance, internal control, early detection, and capacity building significantly contributes to preventing the misuse of village fund management. The positive impacts include the prevention of potential misuse of village funds, increased compliance and understanding of village fund managers regarding regulations, prevention of state financial losses, enhanced community participation, and the realization of more accountable and transparent village governance